SELFISHNESS AND GREED FOR POWER IN POLITICS: A SOCIO-EDUCATIVE VIEW ON SOME OF SHAKESPEARE’S PLAYS - SOEDE, CASIMIR; AKONDO, Dyfaizi Nouhr-Dine; YEKINI, IBRAHIM (My University, 2019)
Abstract Humanity is confronted to many encountered problems. Man enjoys causing problem to his counterpart due to his personal advantages or interest. The selfishness rooted and centered on greediness is deeply present in that evil nature of human being which does not spare his community. Historical rudiments allow us to decipher the author’s plotting of characters along the plays understudy in order to draw our attention of the danger encapsulated in our misconduct and which does not favored our personal and collective development as a unity. Résumé L’humanité est confrontée à d’énormes problèmes. L’homme semble être content lorsqu’il est à l’origine du malheur de son concitoyen à cause de ses avantages et intérêts personnels. L’égoïsme basé sur la gourmandise se voit présent dans le mauvais comportement de l’être humain qui ne fait rien pour y remédier. Les outils historiques nous ont permis d’analyser les comportements des personnages à travers leurs propos le long de la scène dans le but de retenir notre attention sur les dangers qui nous guettent et qui ne présagent du bien pour notre développement personnel et ainsi que celui collectif
Keywords: Unité; le Mauvais; La satisfaction-collective; le patriotisme; la méchanceté; Keywords: Unity; Evil; collective-satisfaction; patriotism; wickedness